E-learning in French language learning: A bibliometric analysis using VOSviewer - Racmadhany, Ariessa; Puspitasari, Feny (LingTera, 2025)
This study investigates the development of French language learning and its relation to e-learning. The study employs a computational approach to bibliometric analysis using VOSviewer. The authors used the Publish or Perish application to collect scholarly sources from Google Scholar over the past ten years (2013–2023). The keywords “E-Learning,” “Educational Application,” and “French Learning” were used to identify relevant articles, resulting in 802 sources related to the topic. The results show that the four most frequently occurring terms are e-learning, French, application, and education. A total of 182 items were identified and grouped into seven clusters. The number of publications fluctuated from 2013 to 2020. In even-numbered years, there was a general increase in publications (56, 59, 66, and 73), while odd-numbered years showed a downward trend (47, 56, 60, and 73). In 2021 and 2022, there was a significant increase to 92 and 126 publications, respectively. In 2023, the number slightly decreased to 94 publications. The results of this study may serve as a foundation for future research on French language learning through e-learning and contribute to the growing body of literature on digital language education.